Metal soft magnetic antirust powder for integrally-formed inductor and coating process

By using rotating low-pressure chemical vapor deposition method to deposit SiO2 film on the surface of FeSiCr magnetic powder, the problem of insufficient anti-rust performance of the integrated molded inductor in humid environments is solved, efficient rust prevention and insulation is achieved, the process is simplified and the resistance is improved.

CN119650235APending Publication Date: 2025-03-18TIZ ADVANCED ALLOY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411818366.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The anti-rust performance of the existing integrated molding inductors is still insufficient in humid environments, and the commonly used coating process is complex and there is a problem of poor anti-rust performance.

Method used

Rotating low-pressure chemical vapor deposition method is used to deposit SiO2 film on the surface of FeSiCr magnetic powder to achieve efficient rust prevention and insulation.

Benefits of technology

Through simplifying the process, the high rust and insulation properties of FeSiCr magnetic powder are achieved, avoiding the oxidative corrosion effect of oxygen on the magnetic powder and improving the overall resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650235A_ABST
    Figure CN119650235A_ABST
Patent Text Reader

Abstract

The invention provides metal soft magnetic rust-proof powder for an integrally-formed inductor and a coating process, FeSiCr magnetic powder is adopted as the metal soft magnetic rust-proof powder, and a SiO2 film is deposited and coated on the surface of the FeSiCr magnetic powder through a rotary low-pressure chemical vapor deposition method. The method has the advantages that a layer of uniform and compact oxide film can be efficiently deposited on the surface of the magnetic powder in a short time in a rotary low-pressure chemical vapor deposition mode, the characteristics of high rust prevention and high insulation are achieved, and the process is simple.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The invention relates to the technical field of magnetic functional materials, and in particular to a metal soft magnetic rust-proof powder for an integrally formed inductor and a coating process. [Background technology]

[0002] One-piece molded inductors are made by embedding windings between insulated metal magnetic powders and die-casting them. They can provide stable power supply under high current conditions. In addition to the inductance value, one-piece molded inductors need to focus on corrosion resistance, voltage breakdown resistance, and insulation properties. Therefore, the selection of powder materials and insulation coating processes for one-piece molded inductors are particularly critical.

[0003] One-piece molded inductors usually use carbonyl iron powder or iron silicon chromium powder as powder materials. These two types of magnetic powders have high saturation magnetic induction intensity, excellent DC bias characteristics and high resistivity. However, the anti-rust performance of iron powder is poor, and it will begin to rust after being exposed to room temperature for 12 hours. Although the iron silicon chromium powder introduces chromium elements through component optimization, the magnetic powder can react with air to form a chromium oxide protective layer on the surface, which improves the anti-rust and corrosion resistance to a certain extent. However, when the device is used in a humid environment, it is still prone to rust problems, which needs to be further improved through insulation coating process. Due to the high toxicity and carcinogenicity of chromate, with the enhancement of environmental awareness, the previously commonly used chromate passivation method has gradually been replaced by phosphoric acid passivation in electronic soft magnetic materials, but phosphoric acid passivation still has the problem of poor anti-rust performance, so it is still necessary to find a new coating process.

[0004] The Chinese invention patent with publication number CN117275927B discloses a rust-proof high-performance soft magnetic powder, which is subjected to a rotary nitriding treatment of the magnetic powder at high temperature by argon and hydrogen to form a nitrided layer on the surface of the magnetic powder, and then coated with a phosphating agent, a coupling agent and a binder in sequence. Although a relatively good rust-proof performance is obtained, the process is very complicated, and the coating process alone has undergone four steps. The Chinese invention patent application with publication number CN112908605A discloses a metal self-rust-proof magnetic powder core, which is immersed in a passivating agent solution again for curing after the magnetic powder core is formed and annealed for secondary insulation. This method can avoid the influence of high-temperature heat treatment on the insulating film, but multiple insulations will greatly affect the magnetic permeability and is not conducive to obtaining high inductance, and new stress will be introduced during the re-curing process.

[0005] In summary, there is an urgent need to develop a high-performance metal soft magnetic powder with simple process and good rust resistance, so that the one-piece molded inductor has both high rust resistance and high insulation. [Summary of the invention]

[0006] The technical problem to be solved by the present invention is to provide a metal soft magnetic rust-proof powder and coating process for one-piece molded inductors. By utilizing the rotating low-pressure chemical vapor deposition method, a uniform and dense oxide film can be deposited on the surface of the magnetic powder in a short time and efficiently, achieving high rust-proof and high insulation properties, and the process is simple.

[0007] The present invention is achieved in that:

[0008] In a first aspect, a metal soft magnetic rust-proof powder for an integrally formed inductor is provided. The metal soft magnetic rust-proof powder is FeSiCr magnetic powder, and a SiO2 film is deposited and coated on the surface of the FeSiCr magnetic powder by a rotary low-pressure chemical vapor deposition method.

[0009] Furthermore, the atomic percentage content of Si in the FeSiCr magnetic powder is 5-6%, and the atomic percentage content of Cr in the FeSiCr magnetic powder is 3-5%.

[0010] Furthermore, the FeSiCr magnetic powder is spherical FeSiCr magnetic powder prepared by an atomization method.

[0011] Furthermore, the atomization method adopts any one of gas atomization, high-temperature gas atomization, water atomization, water-gas combined atomization, and rotary water atomization.

[0012] Furthermore, the particle size of the FeSiCr magnetic powder is 1 to 100 μm.

[0013] In a second aspect, a coating process of a metal soft magnetic anti-rust powder for an integrally formed inductor is provided, the coating process comprising the following steps:

[0014] Step 1, placing FeSiCr magnetic powder in a deposition tube, evacuating the deposition tube and introducing argon gas into the purge pipe;

[0015] Step 2: using a heating device to heat the deposition tube to a preset deposition temperature, and using a stable argon flow rate to make the pressure in the deposition tube reach a preset deposition pressure;

[0016] Step 3, placing the ethyl orthosilicate liquid in a raw material tank, adjusting the argon valve to allow the argon gas to flow through the raw material tank containing the ethyl orthosilicate liquid, and the argon gas carries the ethyl orthosilicate liquid into the deposition tube;

[0017] Step 4, start the deposition tube to rotate, so that the SiO2 film is deposited on the surface of the FeSiCr magnetic powder;

[0018] Step 5: After the deposition of the SiO2 film is completed within the preset reaction time, the heating device and the gas source valve of the ethyl orthosilicate liquid are turned off, and argon gas is introduced into the deposition tube to exhaust the excess reaction gas in the deposition tube; the gas pressure in the deposition tube is restored to normal pressure, the air inlet and outlet of the deposition tube are turned off, and the rotation of the deposition tube is stopped;

[0019] Step 6: Take out the FeSiCr magnetic powder after cooling it in the furnace, and you can get the FeSiCr magnetic powder coated with SiO2 film.

[0020] Furthermore, in step 1, the step of evacuating the deposition tube specifically includes: evacuating the deposition tube to a vacuum degree lower than 1×10 -2 Pa.

[0021] Furthermore, the step 2 is specifically as follows: using a heating device to heat the deposition tube to 700-800° C. at a heating rate of 5-40° C. / min, and using a stable argon flow rate to make the pressure in the deposition tube reach 0-150 Pa.

[0022] Furthermore, in step 4, the rotation speed of the deposition tube is 10 to 40 r / min.

[0023] Furthermore, in step 5, the preset time is 30-90 minutes, and the normal pressure is 101325Pa.

[0024] By adopting the technical solution of the present invention, at least the following beneficial effects are achieved:

[0025] 1. FeSiCr magnetic powder is selected, which has higher intrinsic anti-rust performance than other soft magnetic powders without Cr element, thus helping to improve the anti-rust performance.

[0026] 2. By adopting the low-pressure chemical vapor deposition method, only the gas source used to carry ethyl orthosilicate needs to be introduced for thermal decomposition, without the need to introduce oxygen reaction as in normal-pressure chemical vapor deposition. This can effectively avoid the oxidation and rusting effect of oxygen on FeSiCr magnetic powder, thereby improving the overall resistance of FeSiCr magnetic powder.

[0027] 3. By using the rotary chemical vapor deposition method, SiO2 film can be evenly deposited on the surface of FeSiCr magnetic powder, so that the coated FeSiCr magnetic powder has better rust resistance and insulation properties.

[0028] 4. The coating of FeSiCr magnetic powder can be completed through only one process, and the process is simple.

Brief Description of the Drawings

[0029] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.

[0030] Figure 1 This is a surface morphology of the FeSiCr magnetic powder prepared in Example 1 of the present invention.

[0031] Figure 2 This is a morphology diagram of the FeSiCr magnetic powder obtained in Example 1 of the present invention after being subjected to salt atomization treatment.

[0032] Figure 3 This is a morphology diagram of the FeSiCr magnetic powder obtained in Comparative Example 1 of the present invention after being treated with salt atomization. [Specific implementation method]

[0033] The specific embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although the specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0034] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.

[0035] See also Figures 1 to 3 As shown, the present invention is a metal soft magnetic rust-proof powder for integrally formed inductors, wherein the metal soft magnetic rust-proof powder adopts FeSiCr magnetic powder, and the surface of the FeSiCr magnetic powder is deposited and coated with SiO2 film by rotating low-pressure chemical vapor deposition. The present invention selects FeSiCr magnetic powder, which has higher intrinsic powder rust-proof performance than other soft magnetic powders that do not contain Cr elements; at the same time, the SiO2 film is deposited and coated on the surface of the FeSiCr magnetic powder by rotating low-pressure chemical vapor deposition, that is, the SiO2 film can be uniformly deposited on the surface of the FeSiCr magnetic powder without the introduction of oxygen, which has the advantages of simple operation, good stability, high film uniformity, etc., and the coated FeSiCr magnetic powder has better rust-proof performance and insulation characteristics.

[0036] In the present invention, the atomic percentage content of Si in the FeSiCr magnetic powder is 5-6%, and the atomic percentage content of Cr in the FeSiCr magnetic powder is 3-5%. The addition of Si element in the FeSiCr alloy is beneficial to increase the resistance, thereby reducing the loss of coercive force and inductance; the addition of Cr element can increase the resistance on the one hand, and on the other hand, it can form a dense chromium oxide coating on the surface to improve rust resistance.

[0037] In the present invention, the FeSiCr magnetic powder is a spherical FeSiCr magnetic powder prepared by an atomization method.

[0038] More specifically, the atomization method adopts any one of gas atomization, high-temperature gas atomization, water atomization, water-gas combined atomization, and rotary water atomization. Gas atomization, high-temperature gas atomization, water atomization, water-gas combined atomization, and rotary water atomization are all commonly used atomization methods in the art, and any one of them can be selected according to actual needs during specific implementation.

[0039] In the present invention, the particle size of the FeSiCr magnetic powder is 1 to 100 μm. Generally, the larger the particle size of the magnetic powder, the higher the magnetic permeability and the higher the corresponding loss; while the smaller the particle size of the magnetic powder, the lower the magnetic permeability and the lower the loss; in order to better balance the magnetic permeability and loss, the particle size of the FeSiCr magnetic powder designed in the present invention is 1 to 100 μm.

[0040] The present invention discloses a coating process for a metal soft magnetic rust-proof powder for an integrally formed inductor, the coating process comprising the following steps:

[0041] Step 1, placing FeSiCr magnetic powder in a deposition tube, evacuating the deposition tube and then passing argon gas into the purge pipe; wherein the deposition tube can be a glass deposition tube; at the same time, compared with traditional soft magnetic materials, the present invention uses FeSiCr magnetic powder because the magnetic permeability of FeSiCr alloy is stable, the saturation magnetic induction intensity is high, the DC superposition characteristics are good, and it has excellent anti-rust performance.

[0042] In the specific implementation of the present invention, in step 1, the vacuuming of the deposition tube specifically includes: the vacuum degree of the deposition tube is drawn to less than 1×10 -2 Pa.

[0043] Step 2: Use a heating device to heat the deposition tube to a preset deposition temperature, and use a stable argon flow rate to make the pressure in the deposition tube reach a preset deposition pressure; wherein the heating device can specifically be a muffle furnace.

[0044] When the present invention is implemented, the step 2 is specifically as follows: heating the deposition tube to 700-800°C at a heating rate of 5-40°C / min by using a heating device, and using a stable argon flow rate to make the pressure in the deposition tube reach 0-150Pa. Since the reaction gas of the present invention is introduced after the temperature is stabilized, the heating rate of the present invention will not affect the subsequent coating process. Generally, within the speed regulation range allowed by the equipment, a faster heating rate is selected to save production time. Subsequently, the reaction temperature of low-pressure chemical vapor deposition is generally high, usually higher than 700°C, and the higher the temperature, the faster the deposition rate. Therefore, the present invention heats the deposition tube to 700-800°C; in addition, the increase in pressure during deposition is also conducive to obtaining a higher deposition rate, but when the pressure is too high, it will affect the weight of ethyl orthosilicate, making the prepared SiO2 film very loose, so the deposition pressure should not be too high. The present invention controls the deposition pressure within the range of 0-150Pa, which can ensure the quality of the SiO2 film while increasing the deposition rate.

[0045] Step 3, placing the ethyl orthosilicate liquid in a raw material tank, adjusting the argon valve to allow the argon gas to flow through the raw material tank containing the ethyl orthosilicate liquid, and the argon gas carries the ethyl orthosilicate liquid into the deposition tube;

[0046] Step 4, start the rotation of the deposition tube to deposit a SiO2 film on the surface of the FeSiCr magnetic powder. In the specific implementation of the present invention, the deposition tube can be driven to rotate by a motor drive mechanism, and the deposition tube can drive the FeSiCr magnetic powder to move during the rotation, so that the FeSiCr magnetic powder will be in a suspended state, so that each particle of magnetic powder can be evenly coated.

[0047] In the specific implementation of the present invention, in step 4, the rotation speed of the deposition tube is 10-40 r / min. Theoretically, increasing the rotation speed will have a better effect, but in actual application, the rotation speed should be selected according to the specific conditions of the equipment.

[0048] Step 5: After the deposition of the SiO2 film is completed within the preset reaction time, the heating device and the gas source valve of the ethyl orthosilicate liquid are turned off, and argon gas is introduced into the deposition tube to exhaust the excess reaction gas in the deposition tube; the gas pressure in the deposition tube is restored to normal pressure, the air inlet and outlet of the deposition tube are turned off, and the rotation of the deposition tube is stopped;

[0049] In the specific implementation of the present invention, in step 5, the preset time is 30-90 minutes, and the normal pressure is 101325 Pa. Generally speaking, the thickness of the deposited coating layer can be controlled by controlling the reaction time of the deposition, so the preset time can be adjusted according to actual needs in the actual production process.

[0050] Step 6: Take out the FeSiCr magnetic powder after cooling it in the furnace, and you can get the FeSiCr magnetic powder coated with SiO2 film.

[0051] By adopting the above technical solution of the present invention, at least the following beneficial effects are achieved:

[0052] 1. FeSiCr magnetic powder is selected, which has higher intrinsic anti-rust performance than other soft magnetic powders without Cr element, thus helping to improve the anti-rust performance.

[0053] 2. By adopting the low-pressure chemical vapor deposition method, only the gas source used to carry ethyl orthosilicate needs to be introduced for thermal decomposition, without the need to introduce oxygen reaction as in normal-pressure chemical vapor deposition. This can effectively avoid the oxidation and rusting effect of oxygen on FeSiCr magnetic powder, thereby improving the overall resistance of FeSiCr magnetic powder.

[0054] 3. By using the rotary chemical vapor deposition method, SiO2 film can be evenly deposited on the surface of FeSiCr magnetic powder, so that the coated FeSiCr magnetic powder has better rust resistance and insulation properties.

[0055] 4. The coating of FeSiCr magnetic powder can be completed through only one process, and the process is simple.

[0056] The present invention is further described in detail below in conjunction with some specific embodiments and comparative examples of the present invention:

[0057] Example 1

[0058] Preparation of Fe by water atomization 91 Si5Cr4 magnetic powder is dried and sieved to obtain powder with a particle size between 1 and 50 μm. The sieved FeSiCr magnetic powder is placed in a deposition tube and vacuumed to 8×10 -3Pa, then argon gas is introduced to purge the pipeline. The deposition tube is heated to 750℃ at a heating rate of 10℃ / min. After the temperature stabilizes, the argon gas flow rate is adjusted to make the pressure in the deposition tube reach 50Pa. The ethyl orthosilicate liquid is placed in the raw material tank, and the argon valve is adjusted to allow the argon gas to flow through the raw material tank containing the ethyl orthosilicate liquid, and the argon gas carries the ethyl orthosilicate liquid into the deposition tube. The rotation of the deposition tube is turned on, and the deposition tube is rotated at a speed of 25r / min, so that a uniform SiO2 coating layer is deposited on the surface of the FeSiCr magnetic powder. After 60 minutes of reaction, the deposition of the SiO2 film is completed, the heating equipment and the gas source valve of the ethyl orthosilicate liquid are closed, and argon gas is introduced into the deposition tube to exhaust the excess reaction gas in the deposition tube. After the air pressure in the deposition tube returns to normal pressure, the air inlet and outlet of the deposition tube are closed, and the rotation of the deposition tube is stopped. After the FeSiCr magnetic powder is cooled to room temperature in the deposition tube, it is taken out to obtain the FeSiCr magnetic powder coated with SiO2.

[0059] Example 2

[0060] Preparation of Fe by water atomization 91 Si5Cr4 magnetic powder is dried and sieved to obtain powder with a particle size between 1 and 50 μm. The sieved FeSiCr magnetic powder is placed in a deposition tube and vacuumed to 8×10 -3 Pa, then argon gas is introduced to purge the pipeline. The deposition tube is heated to 750℃ at a heating rate of 10℃ / min. After the temperature stabilizes, the argon gas flow rate is adjusted so that the pressure in the deposition tube reaches 100Pa. The ethyl orthosilicate liquid is placed in the raw material tank, and the argon valve is adjusted so that the argon gas flows through the raw material tank containing the ethyl orthosilicate liquid, and the argon gas carries the ethyl orthosilicate liquid into the deposition tube. The rotation of the deposition tube is turned on, and the deposition tube is rotated at a speed of 25r / min, so that a uniform SiO2 coating layer is deposited on the surface of the FeSiCr magnetic powder. After 90 minutes of reaction, the deposition of the SiO2 film is completed, the heating equipment and the gas source valve of the ethyl orthosilicate liquid are closed, and argon gas is introduced into the deposition tube to exhaust the excess reaction gas in the deposition tube. After the air pressure in the deposition tube returns to normal pressure, the air inlet and outlet of the deposition tube are closed, and the rotation of the deposition tube is stopped. After the FeSiCr magnetic powder is cooled to room temperature in the deposition tube, it is taken out to obtain the FeSiCr magnetic powder coated with SiO2.

[0061] Example 3

[0062] Preparation of Fe by water atomization 91 Si5Cr4 magnetic powder is dried and sieved to obtain powder with a particle size between 1 and 50 μm. The sieved FeSiCr magnetic powder is placed in a deposition tube and vacuumed to 8×10 -3Pa, then argon gas is introduced to purge the pipeline. The deposition tube is heated to 750℃ at a rate of 10℃ / min. After the temperature stabilizes, the argon gas flow rate is adjusted to make the pressure in the deposition tube reach 50Pa. The ethyl orthosilicate liquid is placed in the raw material tank, and the argon valve is adjusted to allow the argon gas to flow through the raw material tank containing the ethyl orthosilicate liquid, and the argon gas carries the ethyl orthosilicate liquid into the deposition tube. The rotation of the deposition tube is turned on, and the deposition tube is rotated at a speed of 25r / min, so that a uniform SiO2 coating layer is deposited on the surface of the FeSiCr magnetic powder. After 30 minutes of reaction, the deposition of the SiO2 film is completed, the heating equipment and the gas source valve of the ethyl orthosilicate liquid are closed, and argon gas is introduced into the deposition tube to exhaust the excess reaction gas in the deposition tube. After the air pressure in the deposition tube returns to normal pressure, the air inlet and outlet of the deposition tube are closed, and the rotation of the deposition tube is stopped. After the FeSiCr magnetic powder is cooled to room temperature in the deposition tube, it is taken out to obtain the FeSiCr magnetic powder coated with SiO2.

[0063] Example 4

[0064] Preparation of Fe by water atomization 91 Si5Cr4 magnetic powder is dried and sieved to obtain powder with a particle size between 1 and 50 μm. The sieved FeSiCr magnetic powder is placed in a deposition tube and vacuumed to 8×10 -3 Pa, then argon gas is introduced into the purge pipeline. The deposition tube is heated to 700℃ at a heating rate of 10℃ / min. After the temperature stabilizes, the argon gas flow rate is adjusted so that the pressure in the deposition tube reaches 50Pa. The ethyl orthosilicate liquid is placed in the raw material tank, and the argon valve is adjusted so that the argon gas flows through the raw material tank containing the ethyl orthosilicate liquid, and the argon gas carries the ethyl orthosilicate liquid into the deposition tube. The rotation of the deposition tube is turned on, and the deposition tube is rotated at a speed of 25r / min, so that a uniform SiO2 coating layer is deposited on the surface of the FeSiCr magnetic powder. After 30 minutes of reaction, the deposition of the SiO2 film is completed, the heating equipment and the gas source valve of the ethyl orthosilicate liquid are closed, and argon gas is introduced into the deposition tube to exhaust the excess reaction gas in the deposition tube. After the air pressure in the deposition tube returns to normal pressure, the air inlet and outlet of the deposition tube are closed, and the rotation of the deposition tube is stopped. After the FeSiCr magnetic powder is cooled to room temperature in the deposition tube, it is taken out to obtain the FeSiCr magnetic powder coated with SiO2.

[0065] Example 5

[0066] Preparation of Fe by water atomization 91 Si5Cr4 magnetic powder is dried and sieved to obtain powder with a particle size between 1 and 50 μm. The sieved FeSiCr magnetic powder is placed in a deposition tube and vacuumed to 8×10 -3Pa, then argon gas is introduced into the purge pipeline. The deposition tube is heated to 800℃ at a heating rate of 10℃ / min. After the temperature stabilizes, the flow rate of argon gas is adjusted so that the pressure in the deposition tube reaches 150Pa. The ethyl orthosilicate liquid is placed in the raw material tank, and the argon valve is adjusted so that the argon gas flows through the raw material tank containing the ethyl orthosilicate liquid, and the argon gas carries the ethyl orthosilicate liquid into the deposition tube. The rotation of the deposition tube is turned on, and the deposition tube is rotated at a speed of 25r / min, so that a uniform SiO2 coating layer is deposited on the surface of the FeSiCr magnetic powder. After 90 minutes of reaction, the deposition of the SiO2 film is completed, the heating equipment and the gas source valve of the ethyl orthosilicate liquid are closed, and argon gas is introduced into the deposition tube to exhaust the excess reaction gas in the deposition tube. After the air pressure in the deposition tube returns to normal pressure, the air inlet and outlet of the deposition tube are closed, and the rotation of the deposition tube is stopped. After the FeSiCr magnetic powder is cooled to room temperature in the deposition tube, it is taken out to obtain the FeSiCr magnetic powder coated with SiO2.

[0067] Comparative Example 1

[0068] Preparation of Fe by water atomization 91 Si5Cr4 magnetic powder is dried and sieved to obtain powder with a particle size between 1 and 50 μm. The sieved FeSiCr magnetic powder is mixed with 0.5wt% phosphoric acid solution (i.e., the amount of phosphoric acid solution is 0.5wt% of the weight of the FeSiCr magnetic powder), fully stirred and dried to obtain phosphated FeSiCr magnetic powder.

[0069] Comparative Example 2

[0070] Preparation of Fe by water atomization 91 Si5Cr4 magnetic powder is dried and sieved to obtain powder with a particle size between 1 and 50 μm. The sieved FeSiCr magnetic powder is mixed with oxygen and calcined at 550° C. for 30 minutes to obtain FeSiCr magnetic powder with surface auto-oxidation coating.

[0071] Comparative Example 3

[0072] Preparation of Fe by water atomization 91 Si5Cr4 magnetic powder is dried and sieved to obtain powder with a particle size between 1 and 50 μm. The sieved FeSiCr magnetic powder is mixed with KH550 coupling agent and ethanol solution, the amount of KH550 coupling agent is 0.5wt% of the weight of the FeSiCr magnetic powder, and after fully stirring for 30 minutes, 0.5wt% of nano-SiO2 particles are added and stirring is continued for 2 hours (that is, the amount of nano-SiO2 particles is 0.5wt% of the weight of the FeSiCr magnetic powder); after drying, SiO2 coupling-coated FeSiCr magnetic powder is obtained.

[0073] Comparative Example 4

[0074] The difference between Comparative Example 4 and Example 1 is that the pressure in the deposition tube during deposition is the same as the atmospheric pressure, i.e., 101325 Pa; the other contents are the same as Example 1.

[0075] Testing: The FeSiCr magnetic powders prepared in the above Examples 1-5 and Comparative Examples 1-4 were subjected to resistance tests and 48-hour salt spray tests; Figure 1 The surface morphology of the FeSiCr magnetic powder prepared in Example 1 is shown, and 10 μm in the figure represents the scale; Figure 2 The powder morphology of Example 1 after the salt spray test is shown. Figure 3 Shown is the powder morphology of Comparative Example 1 after salt spray test.

[0076] The specific test results are shown in the following table:

[0077]

[0078] From the above table and Figures 1 to 3 It can be seen that by adopting the technical solution of the present invention, a uniform SiO2 coating layer can be deposited on the surface of the FeSiCr magnetic powder, which can provide all-round protection for the FeSiCr magnetic powder, thereby effectively improving the rust resistance and insulation properties. In addition, it can be seen from Comparative Example 4 that when the pressure during deposition is selected as normal pressure, that is, when normal pressure vapor deposition is adopted, it is necessary to extend the deposition time and adjust the deposition temperature, otherwise the insulation withstand voltage performance will be reduced due to the slow deposition rate, thereby reducing the rust resistance.

[0079] Although the specific implementation modes of the present invention are described above, those skilled in the art should understand that the specific implementation modes described are only illustrative and are not intended to limit the scope of the present invention. Equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.

Claims

1. A metal soft magnetic rust-proof powder for integrally molded inductors, characterized in that: The metal soft magnetic rust-proof powder is FeSiCr magnetic powder, and the surface of the FeSiCr magnetic powder is coated with a SiO2 film by a rotary low-pressure chemical vapor deposition method.

2. The metal soft magnetic rust-proof powder for integrally molded inductor according to claim 1, characterized in that: The atomic percentage content of Si in the FeSiCr magnetic powder is 5-6%, and the atomic percentage content of Cr in the FeSiCr magnetic powder is 3-5%.

3. The metal soft magnetic rust-proof powder for integrally molded inductor according to claim 1, characterized in that: The FeSiCr magnetic powder is spherical FeSiCr magnetic powder prepared by an atomization method.

4. The metal soft magnetic rust-proof powder for integrally molded inductor according to claim 3, characterized in that: The atomization method adopts any one of gas atomization, high temperature gas atomization, water atomization, water-gas combined atomization, and rotary water atomization.

5. The metal soft magnetic rust-proof powder for integrally molded inductor according to claim 1, characterized in that: The particle size of the FeSiCr magnetic powder is 1-100 μm.

6. A coating process for the metal soft magnetic rust-proof powder for the integrally formed inductor according to any one of claims 1 to 5, characterized in that: The coating process comprises the following steps: Step 1, placing FeSiCr magnetic powder in a deposition tube, evacuating the deposition tube and introducing argon gas into the purge pipe; Step 2: using a heating device to heat the deposition tube to a preset deposition temperature, and using a stable argon flow rate to make the pressure in the deposition tube reach a preset deposition pressure; Step 3, placing the ethyl orthosilicate liquid in a raw material tank, adjusting the argon valve to allow the argon gas to flow through the raw material tank containing the ethyl orthosilicate liquid, and the argon gas carries the ethyl orthosilicate liquid into the deposition tube; Step 4, start the deposition tube to rotate, so that the SiO2 film is deposited on the surface of the FeSiCr magnetic powder; Step 5: After the deposition of the SiO2 film is completed within the preset reaction time, the heating device and the gas source valve of the ethyl orthosilicate liquid are turned off, and argon gas is introduced into the deposition tube to exhaust the excess reaction gas in the deposition tube; the gas pressure in the deposition tube is restored to normal pressure, the air inlet and outlet of the deposition tube are turned off, and the rotation of the deposition tube is stopped; Step 6: Take out the FeSiCr magnetic powder after cooling it in the furnace, and you can get the FeSiCr magnetic powder coated with SiO2 film.

7. The coating process of the metal soft magnetic rust-proof powder for the integrally formed inductor according to claim 6, characterized in that: In step 1, the step of evacuating the deposition tube specifically includes: evacuating the deposition tube to a vacuum degree lower than 1×10 -2 Pa.

8. The coating process of the metal soft magnetic rust-proof powder for the integrally formed inductor according to claim 6, characterized in that: The step 2 is specifically as follows: using a heating device to heat the deposition tube to 700-800° C. at a heating rate of 5-40° C. / min, and using a stable argon flow rate to make the pressure in the deposition tube reach 0-150 Pa.

9. The coating process of the metal soft magnetic rust-proof powder for the integrally formed inductor according to claim 6, characterized in that: In step 4, the rotation speed of the deposition tube is 10-40 r / min.

10. The coating process of the metal soft magnetic rust-proof powder for the integrally formed inductor according to claim 6, characterized in that: In step 5, the preset time is 30-90 minutes, and the normal pressure is 101325Pa.

Citation Information

Patent Citations

  • Metal self-rust-proof magnetic powder core and manufacturing method thereof

    CN112908605A

  • A rust-resistant, high-performance soft magnetic metal powder and its preparation method

    CN117275927B